Rebirth of the Art of Commentary or Unification of the Three Variations of the Armenian Language observations concerning Marc Nichanian’s Commentary “Friedrich Nietzsche: for the Sake of Sovereignty” and translation of Nietzsche’s “Der Antichrist”). - Petrosyan, Silva (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The author of the article appraises Marc Nichanian’s commentary and translation as an attempt to unify the three variations of Armenian language that have emerged historically: Western Armenian, Grabar, Literary Ancient Armenian and Eastern Armenian, as the translation and commentary are written in the Western Armenian but for readers in Armenia and in the classical spelling. The author of the article states that commentary is written in the wide context of the European culture and mentality. The Commentator uses not only modern concepts of newly emerged phenomena but also old Armenian words for a more accurate expression of the involved notions. The author of the article discusses some concepts and expressions and states that as a real act of translation the one under discussion helps us understand ourselves, rethink our past and present authors and shape our Identity in the light of Nietzsche’s struggle for sovereignty.